2022
DOI: 10.1017/s0033291722002112
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in acute and longer-term posttraumatic symptoms following traumatic injury or illness

Abstract: Background Racial/ethnic differences in mental health outcomes after a traumatic event have been reported. Less is known about factors that explain these differences. We examined whether pre-, peri-, and post-trauma risk factors explained racial/ethnic differences in acute and longer-term posttraumatic stress disorder (PTSD), depression, and anxiety symptoms in patients hospitalized following traumatic injury or illness. Methods PTSD, depression, and anxiety symptoms were assessed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Higher assault rates may reflect patient environments with higher rates of violent crime. Analyses of the same dataset found that social determinants of health, such as financial stress and discrimination, were worse in Black patients and were associated with mental health disparities [ 51 ]. Given that interpersonal violence is associated with both physical wounds and mental health problems, these patients require medical interventions targeted at both physical and mental health symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Higher assault rates may reflect patient environments with higher rates of violent crime. Analyses of the same dataset found that social determinants of health, such as financial stress and discrimination, were worse in Black patients and were associated with mental health disparities [ 51 ]. Given that interpersonal violence is associated with both physical wounds and mental health problems, these patients require medical interventions targeted at both physical and mental health symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated lifetime prevalence rate of posttraumatic stress disorder (PTSD) has been reported to be approximately 7% in the United States (Goldstein et al., 2016). Racial differences have been consistently observed, with Black individuals living in the United States (i.e., Black Americans), including those who have been traumatically injured, exhibiting higher rates of PTSD and more severe symptoms compared to other populations (Alegria et al., 2013; Cruz‐Gonzalez et al., 2023; Roberts et al., 2011; Sibrava et al., 2019). Still, these disparities are not well understood.…”
Section: Symptom Trajectories Following Trauma Exposurementioning
confidence: 99%
“…Further work has corroborated these racial differences. Within a longitudinal study design, not only were Black Americans found to have higher PTSD scores than White Americans, but these rates remained relatively unchanged over time (Cruz‐Gonzalez et al., 2023). Other longitudinal research has noted the chronicity of PTSD among Black Americans, showing poorer prognosis and higher levels of symptom severity (Sibrava et al., 2019).…”
Section: Symptom Trajectories Following Trauma Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The extant literature thus suggests that racially/ethnically minoritized individuals may show adaptive counter-regulatory amygdala dynamics (e.g., emotional blunting) to compensate for greater life stress. The race-related structural inequities may partially contribute to recently observed race-related differences in posttraumatic symptoms in the early aftermath of trauma [26,27]. However, to the best of our knowledge, no prior work has directly investigated racial/ethnic differences in connectivity of threat neurocircuitry in the early aftermath of trauma and the potential contributions of structural inequities.…”
Section: Introductionmentioning
confidence: 99%